2019
DOI: 10.3390/ijerph16214272
|View full text |Cite
|
Sign up to set email alerts
|

Social Relationships, Age and the Use of Preventive Health Services: Findings from the German Ageing Survey

Abstract: This paper investigates the associations between social relationships, age and the use of preventive health services among German adults. Data stem from the German Ageing Survey (10,324 respondents). The use of preventive health services was assessed by asking for regular use of flu vaccination and cancer screening in the past years. Predictors of interest were structural (having a partner, size of the social network) and functional aspects of social relationships (perceived informational support) and age. Log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…Distributing information via social media or in workplaces about the potential benefit of rubella antibody testing for adult men may improve their participation rate. Previous reports have also suggested that social relationships [15] and social norms in the workplace [16] are associated with getting vaccinated among adults. Positive attitudes toward rubella vaccination may be amplified among people who share information about the need to be vaccinated.…”
Section: Discussionmentioning
confidence: 94%
“…Distributing information via social media or in workplaces about the potential benefit of rubella antibody testing for adult men may improve their participation rate. Previous reports have also suggested that social relationships [15] and social norms in the workplace [16] are associated with getting vaccinated among adults. Positive attitudes toward rubella vaccination may be amplified among people who share information about the need to be vaccinated.…”
Section: Discussionmentioning
confidence: 94%
“…For the EU-15 countries, the focus has to be on the following policy interventions: A rethinking of passive labor market policies in order to sustain the 55-65-year-old working group, but also to target increases of active labor market policies for this age cohort; keeping up the R&D expenditure, oriented toward labor skills of the 55-64-year-old working group; reconsideration of EDU for 55-64-year-olds, levels 3-8, oriented towards migrants' inclusion in educational programs (since, in these countries, there is a large flow of migrants from developing countries) [73], and also to 55-64-year-olds for native working people by reshaping their skills as requirements are transformed by the emergence of new digital technologies [68,74]; oriented hospital services to boost healthy conditions and perceptions of people, and thus, making them confident in the public health expenditure in the case of child birth and care, therefore indirectly sustaining birth rates and life expectancy; further government health expenditure aimed at tackling the population aging phenomenon correlated with increasing long-term healthcare in the case of the elderly; and promoting and supporting preventive health actions among people aged 55-64 and low-and medium-educated people, since these categories are the most distant from health prevention, as Bremer et al [27] demonstrated. Under these cumulative interventions, labor productivity within developed EU MS will increase, with direct effects on wellbeing and overall economic development [10,20,[35][36][37][38].…”
Section: Results Of the Structural Equation Model (Sem)mentioning
confidence: 99%
“…Withal, increases in health expectancy can be credited to a great degree to education, where, on average, "people with a low level of education can expect to live six years less than those with a high level of education" [10] (p. 12). These findings are explained by the fact that less educated people are less likely to participate in preventive healthcare, as Bremer et al [27] found in the case of Germany. Furthermore, gains in life expectancy in EU-28 MS slowed, on average, between 2011 and 2018 by nearly 50% when compared to previous periods, mainly due to slower improvements and medical breakthroughs in terms of the management of diseases of the circulatory system and treatment of conditions associated with the later stages of life [28][29][30].…”
Section: Health and Agingmentioning
confidence: 87%
“…Furthermore, having acquaintances who had been tested for rubella antibodies promoted positive attitudes toward rubella vaccination. Previous reports have also suggested that social relationships [15] and social norms in the workplace [16] are associated with getting vaccinated among adults. Positive attitudes toward rubella vaccination may be ampli ed among people who share information about the need to be vaccinated.…”
Section: Discussionmentioning
confidence: 94%